2018
DOI: 10.1039/c7ra10906g
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of arctigenin against neuroinflammation and oxidative stress induced by rotenone

Abstract: The present study was to investigate the neuroprotective effect of arctigenin, the major active component of a traditional Chinese medicine “Arctii Fructus”, against PD in a rat model induced by rotenone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…We normalized energy expenditure to lean body mass to eliminate the effect of different body size as a common approach [64,65]; however, a study showed that this is not an appropriate approach because the regression line between body mass and metabolic rate does not have a zero intercept, and is therefore not linear [66]. Instead, using analysis of covariance (ANCOVA) was recommended for normalizing metabolic rate to body mass.…”
Section: Discussionmentioning
confidence: 99%
“…We normalized energy expenditure to lean body mass to eliminate the effect of different body size as a common approach [64,65]; however, a study showed that this is not an appropriate approach because the regression line between body mass and metabolic rate does not have a zero intercept, and is therefore not linear [66]. Instead, using analysis of covariance (ANCOVA) was recommended for normalizing metabolic rate to body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Arctiin is its main active component and accounting for over 5% of Fructus Arctii as stipulated in Chinese Pharmacopoeia [13]. Research indicated that arctigenin has the function of antioxidation, anti-inflammation [14,15], antitumor [16], and neuronprotective activities [17,18]. Recent studies have shown that arctigenin can also suppress renal interstitial fibrosis, repress TGF-β-induced epithelial-mesenchymal transition (EMT) in human lung cancer cells, and attenuate PQ-induced EMT and pulmonary fibrosis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Arctigenin can protect brain from ischemic stroke through inhibiting NLRP3 inflammasome activation ( 24 ). Additionally, arctigenin administration can protect dopaminergic neurons by eliciting potent antioxidant and anti-inflammatory effects and improve behavior changes of Parkinson’s disease ( 25 ). Arctigenin treatment reduced hematoma, gene expressions of inflammatory (IL-6 and TNF-α) and apoptosis (Caspase-3 and Bcl-2), and accelerated wound closure after a stab wound injury, indicating arctigenin possesses neuroprotective effects on brain tissue through anti-inflammatory and anti-apoptotic actions.…”
Section: Introductionmentioning
confidence: 99%